Estudio de factibilidad para la creación de un online grocery shopping de productos de consumo masivo en la ciudad de Quito con entrega a domicilio - Flores Ferrín, Mayra Verónica (2016)
Nowadays, modern companies try to satisfy diverse types of customers by optimizing its resources, being e-commerce a tool to overcome current barriers. It is evident the online market is booming and the likelihood of success in this market is promising. Currently, there is a wide range of products and services through portals that caused both domestic and international access to the world of virtual sales. Similarly, current governmental policies in Ecuador foster the development of productive activities and mechanisms to encourage e-commerce. Based on the aforementioned background, it is necessary to exploit this market by creating a supermarket, without physical branches, selling only through a web page, with delivery in Quito. This idea emerges to provide convenience, speed, quality and good service to the final customer, showing it is not necessary to travel long distances toward a particular establishment. Instead, the customer can just visit the website to find what he or she wants or needs. External forces can affect new businesses initiated in the market, as the proposed here. Therefore, industry, environment and competition analyses are required so that a clear perspective of access probability to the world of virtual sales can be given at the end. The methodology employed to carry out this research includes primary and secondary sources, which allow designing marketing and sale strategies properly. The market assessments permit to gather information to define relevant data regarding real necessity of an online sale service, quantifying satisfaction level and buying habits at the same time. As a final step, a detailed financial evaluation is carried out so that NPV and IRR can confirm profitability of the new business as well as to identify the payback period and sustainability of the investment.